1999
DOI: 10.1159/000054468
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endocannabinoids and Cannabinoid CB<sub>1</sub> Receptor mRNA in the Pituitary Gland

Abstract: Most data on effects of natural and synthetic cannabinoids on anterior pituitary hormone secretion point out to a primary impact on the hypothalamus. There is also some evidence, however, of possible direct actions of these compounds on the anterior pituitary, although the presence of cannabinoid receptors in the pituitary has not been documented as yet. In the present study, we evaluated the presence of cannabinoid CB1 receptor-mRNA transcripts in the pituitary gland by in situ hybridization. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 35 publications
7
53
1
5
Order By: Relevance
“…One particular brain region highly linked to appetite and metabolism regulation is the hypothalamus. The endocannabinoids anandamide and 2-AG and the CB1 receptors have been localized in this area (21,26,36,54). Although autoradiographic experiments have shown a relatively low density of these receptors in the hypothalamus, their coupling efficiency is as high as or even higher than that observed in more receptor-dense areas (9).…”
Section: Discussionmentioning
confidence: 94%
“…One particular brain region highly linked to appetite and metabolism regulation is the hypothalamus. The endocannabinoids anandamide and 2-AG and the CB1 receptors have been localized in this area (21,26,36,54). Although autoradiographic experiments have shown a relatively low density of these receptors in the hypothalamus, their coupling efficiency is as high as or even higher than that observed in more receptor-dense areas (9).…”
Section: Discussionmentioning
confidence: 94%
“…CB 1 receptors have been detected not only in the hypothalamus (22) , but also in other brain areas involved in the control of food intake, including the nucleus accumbens shell (23) . Recent findings reported by Sano et al (24) demonstrated that D…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, when we looked at the number of pellets and amount of food consumed per session in the present study, we found a significant increase after THC administration and a significant decrease after rimonabant administration. In addition, high levels of endocannabinoids are present in brain areas involved in the regulation of food intake such the hypothalamus (Gonzalez et al, 1999;Howlett, 2002) and the levels of endocannabinoids are under the control of leptin, a main hormone responsible for negative regulation of food intake (Di Marzo et al, 2001).…”
Section: Discussionmentioning
confidence: 99%